2021
DOI: 10.1108/jadee-01-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Food shopping, preparation and consumption practices in times of COVID-19: case of Lebanon

Abstract: PurposeRight after announcing the first cases, several governments worldwide have implemented stringent measures to stop the spread of COVID-19. This disruption in individuals' daily routines transformed food consumption habits. Accordingly, the purpose of this paper is to examine the effects of the COVID-19 pandemic on food consumption, diet and food shopping behaviors in Lebanon.Design/methodology/approachThe paper draws upon an online survey in Lebanon administered in Arabic and English through the Survey M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…These behavioral shifts may affect attitudes and behaviors related to food consumption (18). In this context, many articles show that the COVID-19 pandemic induced changes in food-related behaviors (19)(20)(21)(22). Indeed, the pandemic has influenced food access and shopping behavior (23), food consumption habits and diets (24)(25)(26)(27)(28), as well as food wastage behavior (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These behavioral shifts may affect attitudes and behaviors related to food consumption (18). In this context, many articles show that the COVID-19 pandemic induced changes in food-related behaviors (19)(20)(21)(22). Indeed, the pandemic has influenced food access and shopping behavior (23), food consumption habits and diets (24)(25)(26)(27)(28), as well as food wastage behavior (29).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the pandemic has influenced food access and shopping behavior (23), food consumption habits and diets (24)(25)(26)(27)(28), as well as food wastage behavior (29). However, the COVID-19 pandemic effects are not alike across countries (11,21,27,28,30). El Bilali (31) argues that the pandemic is significantly affecting developing countries and vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%
“…This study enhanced the theoretical background of local and healthy food. First, several studies have argued that local food consumption is more important than ever, during the COVID-19 pandemic (Ben Hassen et al, 2021b;Cranfield, 2020;Duda-Chodak et al, 2020;Naja and Hamadeh, 2020;Rizou et al, 2020). Other studies have argued that this growth is because local food is safe, healthy, and accessible (Aprile et al, 2016;Arsil et al, 2018;Meyerding et al, 2019;Ozturk and Akoglu, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In this context of global breakdown and interruption of international transport, local food became the single viable alternative. Indeed, several studies conducted during the COVID-19 pandemic confirmed the growth of local food consumption amidst the pandemic (Ben Hassen et al, 2021b;Celimli and Adanacioglu, 2021;Duda-Chodak et al, 2020;Loiseau et al, 2020;Mesić et al, 2020). However, to the best of our knowledge, no studies have examined the factors driving this growth.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, the pandemic had several impacts on diet and food behavior. Moreover, COVID-19 is a worldwide pandemic that created a global economic and financial crisis (2), which is expected to seriously affect food access, diet quality, and diversity (9,10).…”
Section: Introductionmentioning
confidence: 99%